Competitividade externa e saldos comerciais da indústria agroalimentar no brasil - Oliveira , Patrícia Borges de (2005)
This paper aims to analyze the dynamics and nature of the main products of the Brazilian agrifood sector in the recent period (1997 to 2002), according to analyzes of the competitiveness indexes - market shares (MS), revealed comparative advantages (VCR) and index. Balance Contribution (CS) and Competitiveness Matrix - according to the Standard International TradeClassification (SITC) classification, at a 4-digit aggregation level. Our most relevant conclusion, based on a competitiveness analysis and the pattern of specialization of the main Brazilian agri-food sectors through the competitiveness indicators MS, VCR, CS and competitiveness matrix, indicate that even with high comparative advantages and market shares, These sectors have a low contribution to the country's trade balance due to the non-convergence of these products to the dynamics of the international market. In other words, exports from selected agri-food sectors (soy, meat, orange juice, coffee and sugar) have been increasing in products whose share in the international market is decreasing or even regressing.